Does Higher Education Make You More Entrepreneurial? Causal Evidence from China - Bin Huang; Massimiliano Tani; Yu Zhu (Institute of Labor Economics (IZA), 2021)
Using the 2017 China Household Finance Survey (CHFS), we estimate the effect of higher education on entrepreneurship for prime-aged males. We distinguish between own-account workers and employers of small and large businesses, respectively, and use the higher education expansion in China starting in 1999 and instruments of pre-school hukou status to help identify causal effects. While our Inverse Probability Weighted Regression Adjustment estimates show that people with more education are less likely to enter entrepreneurship in general, obtaining any qualification beyond the baseline of compulsory schooling significant increases large business ownership later in life, with the maximum effect corresponding to a 3-fold increase found for university graduates. We attribute this effect to graduates taking full advantage of the opportunities presented by access to education earlier on in their lives.
Keywords: I25; J24; L26; 330; higher education; entrepreneurship; higher education expansion; China; Inverse Probability Weighted Regression Adjustment (IPWRA)